2018
DOI: 10.1101/246454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic role of sFRP2 in P53-mutant osteosarcoma development via autocrine and paracrine mechanism

Abstract: Osteosarcoma (OS), the most common primary bone tumor, is highly metastatic with high chemotherapeutic resistance and poor survival rates. Using induced pluripotent stem cells (iPSCs) generated from Li-Fraumeni syndrome (LFS) patients, we investigated an oncogenic role of secreted frizzled-related protein 2 (sFRP2) in P53 mutation-associated OS development. Interestingly, we found that high sFRP2 expression in OS patient samples correlates with poor survival. Systems-level analyses identified that expression o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…In a follow up-study we identified SFRP2 as an autocrine and paracrine factor involved in P53 mutation-mediated osteosarcomagenesis. Using genome-editing we confirmed a correlation between various P53 mutations and increased SFRP2 expression in iPSC and embryonic stem cell derived osteoblasts ( 54 ) and Kim et al (under review).…”
Section: Genome Editingsupporting
confidence: 71%
“…In a follow up-study we identified SFRP2 as an autocrine and paracrine factor involved in P53 mutation-mediated osteosarcomagenesis. Using genome-editing we confirmed a correlation between various P53 mutations and increased SFRP2 expression in iPSC and embryonic stem cell derived osteoblasts ( 54 ) and Kim et al (under review).…”
Section: Genome Editingsupporting
confidence: 71%
“…On the other hand, inhibition of SFRP2, FoXM1 or CYR61 suppresses the tumorigenic process. This demonstrates that the oncogenic role of SFRP2 in OS development is due to its ability to induce oncogenic molecules such as FOXM1 and CYR61 in the presence of mutations in the TP53 gene (44).…”
Section: Role Of Dna Changesmentioning
confidence: 88%
“…This abnormal differentiation of pre-osteoblasts resulted in their transformation into osteosarcoma-like cells. Overexpression of sFRP2 affected angiogenesis, a critical phenomenon in cancer invasion and metastasis, and a transcriptomic analysis revealed that sFRP2 overexpression increased the expression of pro-angiogenic and anti-apoptotic genes in endothelial cells [85]. Consistent with these results, Techavichit et al [86] showed the implication of sFRP2 in invasion and metastasis.…”
Section: Using Sfrps In Cancer Therapy?mentioning
confidence: 72%
“…In contrast, Kim et al [85] studied the effect of sFRP2 overexpression in patients with the Li-Fraumeni syndrome, which is characterized by a p53 mutation and an increased incidence of osteosarcoma (500fold higher in comparison with the normal Fig. 9.…”
Section: Using Sfrps In Cancer Therapy?mentioning
confidence: 99%